(untitled) (Fiep Bulletin - online, 2011)
Although tuberculosis is one of the oldest diseases afflicting humanity, it is not a disease of the past and now needs a new look. So the active pursuit of respiratory symptoms (SR), early diagnosis, completion of treatment and prevention of disease, are measures that need to be completed for the reduction and eventual eradication of TB. Our review aimed to find articles in the literature to refer to techniques used in diagnosis of the disease and assess what the most advantageous method for the detection of TB, seeking a faster result and concrete, since early diagnosis appears as an important measure for the control of TB transmission. The survey was conducted in VHL through descriptors: Tuberculosis and TB / sputum, and found 137 articles, of which only 12 were selected because they meet our criteria for inclusion. It has been found in the study that 50% of the literature cites the smear as the most used and effective in controlling the disease, PCR, in a ratio of 33.4% was mentioned in articles, the chest X-8, 3% and 8.3% refer to other types of diagnosis. Of all the methods analyzed to diagnose TB in this study, the sputum smear microscopy as the method of choice and effective method for detecting the disease, since it is efficient both for its rapidity and the cost.